The difficulties in memorizing literary texts with fourth grade students from teachers’ point of view of and students (Journal of the College of Education for Women, 2019)
The current research seeks to know the difficulties in memorizing literary texts with fourth grade students from teachers’ point of view of and studentsThe research contains a community of (10,870) students from schools affiliated to the Directorate of Karkh, second and the number of schools for boys and girls (79) School and the number of teachers (349) who are specialized in teaching Arabic language to fourth grade preparatory students and there was a section of a randomly sample of each of the students, teachers and schools .Some actions which can be listed below:-The survey which was done by the researcher for the views of the two samples from teachers and students as the number of teachers covered in this research (20) and a school teacher, and (50) students with regard to the difficulties in memorizing literary texts among the students of the fourth secondary grade.2- The researcher classified difficulties that have been reached through a survey of the views of the two samples from teachers, students and some of the literary works from ten magazines and from two questionnaires (34) for teachers and (34) items for students.3- The researcher exhumed the surface honesty for the two questionnaires by presenting this to a group of experts and extracted their stability depending on each area of questionnaires.4- The researcher applied a questionnaire for teachers on the amount of main research sample (40), teachers and a school for students on the main research sample amounting to (140) students spread over 11 high school and in the province of Baghdad / Karkh, second.5- The data were statistically treated by using the Person correlation coefficient and the weighted average, standard deviation and weight percentile and percentage. The researcher reached according to the teachers’ questioners to the below results:The burdens on the teachers shoulder (the number of lectures, administrative work ... etc.) that hinder the follow-up to save the students.Twice the students' interest to conservation. The rely on the written exam only in the estimation of the degree of the student.Whereas the students’ questioners spotted difficulties. And the most important difficulties are:-Lack of motivations which encourage me to memorize literary texts. The prescribed texts don’t care about the differences between the levels of student mentality. The teacher depends on one way of teaching literature and texts. The lack of the allocated mark to memorize the literary texts.